2015
DOI: 10.1038/cddis.2015.218
|View full text |Cite
|
Sign up to set email alerts
|

RAC3 more than a nuclear receptor coactivator: a key inhibitor of senescence that is downregulated in aging

Abstract: Receptor-associated coactivator 3 (RAC3) is a nuclear receptor coactivator usually overexpressed in tumors that exerts oncogenic functions in the cytoplasm and the nucleus. Although as part of its oncogenic actions it was previously identified as an inhibitor of apoptosis and autophagy, its expression is required in order to preserve the pluripotency and embryonic stem cell self-renewal. In this work we investigated its role in cellular senescence. We found that RAC3 overexpression in the nontumoral HEK293 cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 59 publications
(102 reference statements)
1
12
0
Order By: Relevance
“…The loss of normal functionality that results from the induction of senescence has been implicated in age-related diseases and tissue degeneration. 31 , 32 , 33 By comparing cartilage tissues that were harvested from the same OA knee joint that displayed different levels of degeneration, we found that the level of leptin was homogeneous and that the impact of leptin was variable. We observed more serious degeneration in cartilage tissues (low Coll-2 expression) with higher Ob-Rb expression (which activates the leptin pathway), higher p53/p21 expression (which induces tissue senescence) and lower Sirt1 expression in the same knee joint ( Figures 6a and b ).…”
Section: Discussionmentioning
confidence: 96%
“…The loss of normal functionality that results from the induction of senescence has been implicated in age-related diseases and tissue degeneration. 31 , 32 , 33 By comparing cartilage tissues that were harvested from the same OA knee joint that displayed different levels of degeneration, we found that the level of leptin was homogeneous and that the impact of leptin was variable. We observed more serious degeneration in cartilage tissues (low Coll-2 expression) with higher Ob-Rb expression (which activates the leptin pathway), higher p53/p21 expression (which induces tissue senescence) and lower Sirt1 expression in the same knee joint ( Figures 6a and b ).…”
Section: Discussionmentioning
confidence: 96%
“…Modifications of microRNAs , signalling or autophagy correlated with ageing determine various structural and physiological changes of the arterial wall that predispose it to atherosclerosis. In particular, inversion of the elastin/collagen ratio and the nonenzymatic glycosylation of some proteins present in the arterial wall, such as collagen, capable of cross‐linking adjacent proteins increase the mechanical vessel rigidity and stiffness.…”
Section: Age‐related Modifications Of the Arterial Wall And Atherosclmentioning
confidence: 99%
“…However, although RAC3 overexpression significantly decreased the IC 50 , the curve of biological response was modified, reaching higher maximal values of cell death. This unexpected result for Oxa concentrations higher than 0.4 μM could be probably explained regarding the anti-senescent and proliferative stimulating role of RAC3 [ 33 ], which perhaps could be increasing the number of cells capable to respond to Oxa stimulation. Therefore, taking together all these results clearly demonstrate that the expression levels of RAC3 may influence the sensitivity to chemotherapeutic drugs, increasing the chemoresistance when is overexpressed.…”
Section: Resultsmentioning
confidence: 99%